In Vitro, In Vivo and In Silico Assessment of the Antimicrobial and Immunomodulatory Effects of a Water Buffalo Cathelicidin (WBCATH) in Experimental Pulmonary Tuberculosis - Jacqueline Barrios Palacios; Jorge Barrios-Payán; Dulce Mata-Espinosa; Jacqueline V. Lara-Espinosa; Juan Carlos León-Contreras; Gerald H. Lushington; Tonatiuh Melgarejo; Rogelio Hernández-Pando (MDPI AG, 2022)
Tuberculosis (TB) is considered the oldest pandemic in human history. The emergence of multidrug-resistant (MDR) strains is currently considered a serious global health problem. As components of the innate immune response, antimicrobial peptides (AMPs) such as cathelicidins have been proposed to have efficacious antimicrobial activity against Mycobacterium tuberculosis (Mtb). In this work, we assessed a cathelicidin from water buffalo, Bubalus bubalis, (WBCATH), determining in vitro its antitubercular activity (MIC), cytotoxicity and the peptide effect on bacillary loads and cytokines production in infected alveolar macrophages. Our results showed that WBCATH has microbicidal activity against drug-sensitive and MDR Mtb, induces structural mycobacterial damage demonstrated by electron microscopy, improves Mtb killing and induces the production of protective cytokines by murine macrophages. Furthermore, in vivo WBCATH showed decreased bacterial loads in a model of progressive pulmonary TB in BALB/c mice infected with drug-sensitive or MDR mycobacteria. In addition, a synergistic therapeutic effect was observed when first-line antibiotics were administered with WBCATH. These results were supported by computational modeling of the potential effects of WBCATH on the cellular membrane of Mtb. Thus, this water buffalo-derived cathelicidin could be a promising adjuvant therapy for current anti-TB drugs by enhancing a protective immune response and potentially reducing antibiotic treatment duration.